Digital Inclusion or Digital Divide for Older Immigrants? A Scoping Review - Chen, Xin; Östlund, Britt; Frennert, Susanne ; 0000-0002-9522-5469 (6th International Conference on Human Aspects of IT for the Aged Population, ITAP 2020, held as part of the 22nd International Conference on Human-Computer Interaction, HCII 2020, Copenhagen, Denmark, 2020-07-19 - 2020-07-24, 2020)
The discussion of the digital divide and digital inclusion has extended to older adults. Although knowledge on the digital divide and digital inclusion among native older adults has increased substantially, little is known about the situations of older immigrants in relation to the digital divide. This paper employed the scoping review approach to map the situations and research methods of the digital divide among older immigrants from recent empirical studies. The initial search identified 997 articles, of which 13 articles were selected for this review. The results showed that socioeconomic status, language proficiency, degree of acculturation, level of education, and digital literacy are the most common factors leading to the disparities between native older adults and older immigrants. Although the results showed a narrowing gap as concerns access to the Internet, interventions are needed to reduce the divide among individuals of different ethnicities due to disparities in digital skills and knowledge. The included studies applied quantitative, qualitative, and mixed-method approaches. The homogeneity of the findings of some included studies implied the need to develop more methods and models to study the digital divide among older immigrants. This review suggested that future research incorporate ethnic characteristics in the research design to provide in-depth knowledge about the ethnic group. This knowledge could potentially be utilized for future interventions aimed at narrowing the remaining gap of the digital divide.
Publisher Copyright: © 2020, Springer Nature Switzerland AG.
Keywords: Digital divide; Digital inclusion; Digitalization; Older immigrant